PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD DAN PENDEKATAN CRT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA - Anisa Husnul Khotimah; Budiyono; Hapsari Dewi; Yunita Wulandari; Ahmad Rifaldi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Different learning strategies are needed to increase students' motivation in learning mathematics. It is also important to integrate local culture into the educational process, so that students can understand the relationship between mathematical concepts and their environment. This research aims to improve student learning outcomes by implementing the STAD type cooperative learning model and the Culturally Responsive Teaching (CRT) approach. The learning media used are Powerpoint and the Wordwall application as teaching materials for whole number counting operations in class VI at SD Labschool Unesa 2. This research uses Kurt Lewin's paradigm in the form of classroom action research (PTK). The research was carried out in two cycles, where each cycle consisted of four stages, namely planning, action, observation and reflection. Based on research data from cycle I, there was an increase in learning outcomes by 60.87% and a decrease in the number of incomplete students by 9 people. Learning outcomes increased to 86.96% in cycle II, there were 3 students who were declared incomplete. The application of the CRT approach and STAD model supported by PowerPoint media and the Wordwall application succeeded in improving student learning outcomes in whole number counting operations material in class VI at SD Labschool Unesa 2.